The use of AI (artificial intelligence) for teaching english in higher medical institutions - Oleksiienko, A. V.; Олексієнко, Алла Валеріївна (Запорізький державний медико-фармацевтичний університет, 2023)
The aim of the investigation is to determine the advantages and disadvantages of using resources based on artificial intelligence based on the resource “Magicschool.ai”.